Portuguese children dietary exposure to multiple mycotoxins – An overview of risk assessment under MYCOMIX project. (August 2018) - Assunção, Ricardo; Martins, Carla; Vasco, Elsa; Jager, Alessandra; Oliveira, Carlos; Cunha, Sara C.; Fernandes, José O.; Nunes, Baltazar; Loureiro, Susana; Alvito, Paula
Abstract: Mycotoxins are secondary fungi metabolites that induce acute and chronic toxic effects in humans and animals. Simultaneous contamination of cereal-based products by multiple mycotoxins has been increasingly reported, including in food products usually consumed by children. Although some previous authors assessed the health risk of children exposed to multiple mycotoxins, scarce data are available on the risk associated with the ingestion of multiple mycotoxins through different food products. MYCOMIX, a national funded project, intended to contribute to fill this gap. The present study aimed to overview the risk assessment of multiple mycotoxins performed under MYCOMIX, assessing for the first time, the risk associated with the exposure to 13 mycotoxins in breakfast cereals, infant cereals and biscuits consumed by children from Lisbon region, Portugal. Results on mycotoxins occurrence showed that 94% of samples were contaminated with at least one mycotoxin, although at levels below the legislated limits. Co-contamination was observed in 75% of the analysed samples. Estimated aflatoxins exposure suggested a potential adverse health effect for percentiles of intake above or equal to P50. The obtained results suggested that future research actions should be set in motion in order to protect children health. Graphical abstract: Highlights: Risk of Portuguese children exposed to multiple mycotoxins was evaluated under MYCOMIX project. 94% of cereal-based products were contaminated with at least one mycotoxin. 75% of analysed samples were contaminated with two or more mycotoxins. Aflatoxins exposure suggested potential adverse health effect for P50 or higher. Mycotoxins present in food usually consumed by young children could constitute a risk for children's health.